Efeitos da suplementação com creatina na asma - Sousa, Adilson Santos Andrade de (2014)
In the recent years, an increasing number of studies investigating the effects of creatine supplementation not only for athletes and sportsmen, but also for various diseases have emerged. Its use is very common among athletes, in order to gain strength and fat free muscle mass. Some studies also suggested that creatine has anti-inflammatory and antioxidant action on skeletal muscle. On the other hand, some studies have shown that creatine supplementation, when not accompanied by physical exercise, may worsen lung allergic inflammatory response, such as asthma. However, the possible mechanisms mediating the effects of creatine supplementation on pulmonary allergic inflammation has not been fully elucidated. Therefore, the present study evaluated the possible effects of creatine supplementation in an experimental model of asthma using ovalbumin as antigen in BALB/c mice. It was studied the effects of creatine supplementation on leukocyte infiltration in the perivascular space and the activation of perivascular leukocytes, beyond the activation of cells of the pulmonary vascular wall. The study was conducted using 48 BALB/c mice divided into 4 groups of 12 animals in each group, as follow: Control (Co), Creatine (Cr), OVA (OVA) and Creatine+OVA (OVA+Cr). The creatine supplementation showed a reduction in the inflammatory infiltrate in the perivascular space as well as the reduction in the expression of some markers in inflammatory mediators in the vascular wall. However, for some markers an opposite effect was observed, since that the expression of these markers displayed increased compared with OVA and Control groups. Also, creatine supplementation reduced the expression of reactive oxygen and nitrogen species. We conclude that creatine supplementation reduces the inflammatory process of asthma by reduction of oxidative stress. However, more studies are needed to elucidate the mechanisms involved.